Engineering of Tracheal Grafts Based on Recellularization of Laser-Engraved Human Airway Cartilage Substrates. (February 2022) - Baranovskii, Denis; Demner, Jan; Nürnberger, Sylvia; Lyundup, Alexey; Redl, Heinz; Hilpert, Morgane; Pigeot, Sebastien; Krasheninnikov, Michael; Krasilnikova, Olga; Klabukov, Ilya; Parshin, Vladimir; Martin, Ivan; et al.
Objective: Implantation of tissue-engineered tracheal grafts represents a visionary strategy for the reconstruction of tracheal wall defects after resections and may develop into a last chance for a number of patients with severe cicatricial stenosis. The use of a decellularized tracheal substrate would offer an ideally stiff graft, but the matrix density would challenge efficient remodeling into a living cartilage. In this study, we hypothesized that the pores of decellularized laser-perforated tracheal cartilage (LPTC) tissues can be colonized by adult nasal chondrocytes (NCs) to produce new cartilage tissue suitable for the repair of tracheal defects. Design: Human, native tracheal specimens, isolated from cadaveric donors, were exposed to decellularized and laser engraving–controlled superficial perforation (300 μm depth). Human or rabbit NCs were cultured on the LPTCs for 1 week. The resulting revitalized tissues were implanted ectopically in nude mice or orthotopically in tracheal wall defects in rabbits. Tissues were assayed histologically and by microtomography analyses before and after implantation. Results: NCs were able to efficiently colonize the pores of the LPTCs. The extent of colonization (i.e., percentage of viable cells spanning >300 μm of tissue depth), cell morphology, and cartilage matrix deposition improved once the revitalized constructs were implanted ectopically in nude mice. LPTCs could be successfully grafted onto the tracheal wall of rabbits without any evidence of dislocation or tracheal stenosis, 8 weeks after implantation. Rabbit NCs, within the LPTCs, actively produced new cartilage matrix. Conclusion: Implantation of NC-revitalized LPTCs represents a feasible strategy for the repair of tracheal wall defects.